2001
DOI: 10.1016/s0893-133x(01)00231-7
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method to Measure Baseline Occupancy of Neostriatal Dopamine D2 Receptors by Dopamine In Vivo in Healthy Subjects

Abstract: The effect of endogenous dopamine (DA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 52 publications
5
74
2
Order By: Relevance
“…For example, aMPT requires repeated administration and a minimum of 3 days in-hospital observation (Verhoeff et al, 2001); its administration can induce crystalluria (Brogden et al, 1981) and acute dystonic reactions (McCann et al, 1990). In comparison, APTD can induce measurable effects within 3 h Figure 3 Correlation between plasma levels of tyrosine, following phenylalanine/tyrosine depletion, and the ability of d-amphetamine to elicit DA release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, aMPT requires repeated administration and a minimum of 3 days in-hospital observation (Verhoeff et al, 2001); its administration can induce crystalluria (Brogden et al, 1981) and acute dystonic reactions (McCann et al, 1990). In comparison, APTD can induce measurable effects within 3 h Figure 3 Correlation between plasma levels of tyrosine, following phenylalanine/tyrosine depletion, and the ability of d-amphetamine to elicit DA release.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the increased [ 11 C]raclopride BP on the APTD test session might have reflected an upregulation of DA D2 receptors. aMPT increases striatal binding of [ 11 C]raclopride (Verhoeff et al, 2001), [ 123 I]IBZM (Laruelle et al, 1997a), and [ 123 I]epidepride (Fujita et al, 2000). However, these changes are thought to reflect aMPT-induced decreases in synaptic DA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Acute dopamine depletion is possible in humans via administration of the tyrosine hydroxylase inhibitor alpha-methyl-para-tyrosine (AMPT). Challenges with AMPT have been successfully employed in conjunction with PET to estimate endogenous dopamine levels at D 2/3 R in living humans (Caravaggio et al, 2015;Caravaggio et al, 2014;Kegeles et al, 2010;Laruelle et al, 1997;Martinez et al, 2009;Verhoeff et al, 2001). Thus, measuring glutamate concentrations with 1 H-MRS before and after AMPT administration could help elucidate how dopamine depletion alters glutamatergic functioning in healthy persons and persons with neuropsychiatric diseases.…”
Section: Future Directions and Limitationsmentioning
confidence: 99%
“…However, a negative correlation was observed between glutamate concentrations in the left prefrontal cortex and dopamine synthesis capacity in the left ventral striatum (r 2 = .17). Future PET studies examining dopamine synthesis capacity or endogenous dopaminergic tone (Caravaggio et al, 2014;Laruelle et al, 1997;Verhoeff et al, 2001) should also examine glutamate concentrations measured with 1 H-MRS in the dorsal striatum and cortex; in healthy persons and persons with neuropsychiatric diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In a D 2 ligand-binding PET study using 11 C-raclopride in healthy volunteers, AMPT impaired attention, which was associated with increased raclopride binding potential, whereas psychomotor speed remained unchanged. 102 This study did not include a placebo condition, but can nevertheless be taken to indicate that the effects of AMPT on cognitive performance are associated with lowered DA function. Another study reported decreased performance on memory and attention tasks relative to lactose administration when AMPT was followed by 40 h sleep deprivation, but the effects were not significant after AMPT or sleep deprivation alone.…”
Section: Acute Tryptophan Depletionmentioning
confidence: 99%